Fabrication of Iron Pyrite Thin Films and Photovoltaic Devices by Sulfurization in Electrodeposition Method - Zheng Lu (MDPI AG, 2021)
Iron pyrite is a cheap, stable, non-toxic, and earth-abundant material that has great potential in the field of photovoltaics. Electrochemical deposition is a low-cost method, which is also suitable for large-scale preparation of iron pyrite solar cells. In this work, we prepared iron pyrite films by electrochemical deposition with thiourea and explored the effect of sulfurization on the synthesis of high-quality iron pyrite films. Upon sulfurization, the amorphous precursor film becomes crystallized iron pyrite film. Optical and electrical characterization show that its band gap is 0.89 eV, and it is an n type semiconductor with a carrier concentration of 3.01 × 1019 cm−3. The corresponding photovoltaic device shows light response. This work suggests that sulfurization is essential in the electrochemical preparation for fabricating pure iron pyrite films, and therefore for low-cost and large-scale production of iron pyrite solar cells.